Unpacking the policy implementation in Islamic schools: A case of MAN 1 Kudus Indonesia - Abadi, Nur; Alfayn, Mukhammad Akhmad Najich (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2025)
This qualitative case study investigates the complex dynamics of policy implementation within Islamic educational institutions in Indonesia, focusing on the